2021
DOI: 10.5603/fm.a2020.0057
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral triple mandibular canal with double mandibular foramen: cone-beam computed tomography findings of an unexpected anatomical variant

Abstract: The mandibular canal is a bony channel located within the spongiosa of the mandible. The main structure contained in the mandibular canal is the inferior alveolar nerve (IAN). The IAN is a very important structure that requires due consideration during dental or surgical procedures involving the mandible. Therefore, a detailed morphological analysis of the mandibular canal should be carried out before any surgical procedure in the mandibular region in order to avoid complications and to reduce the risk of inad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
(32 reference statements)
2
2
0
Order By: Relevance
“…Previous radiographic studies reported various prevalence rates for MCB, ranging from 0% to 38.7% in panoramic and from 9.8% to 66.5% in CBCT assessments. 3,18,20,[22][23][24] The prevalence rate of 43.7% in this study is relatively high and similar to the values reported by Okmus and Dumlu, 8 de Castro et al, 20 15 reported high prevalence rates of 66.5% and 65%, respectively, for bifid mandibular canals.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Previous radiographic studies reported various prevalence rates for MCB, ranging from 0% to 38.7% in panoramic and from 9.8% to 66.5% in CBCT assessments. 3,18,20,[22][23][24] The prevalence rate of 43.7% in this study is relatively high and similar to the values reported by Okmus and Dumlu, 8 de Castro et al, 20 15 reported high prevalence rates of 66.5% and 65%, respectively, for bifid mandibular canals.…”
Section: Discussionsupporting
confidence: 87%
“…The prevalence of MCB was calculated as 43.7% (131 out of 300 patients) in the present sample. Previous radiographic studies reported various prevalence rates for MCB, ranging from 0% to 38.7% in panoramic and from 9.8% to 66.5% in CBCT assessments 3,18,20,22–24 . The prevalence rate of 43.7% in this study is relatively high and similar to the values reported by Okmus and Dumlu, 8 de Castro et al, 20 and Orhan et al 2 (40%, 41.1%, and 46.5%, respectively).…”
Section: Discussionsupporting
confidence: 86%
“…The mandibular canal, nowadays referred to as the inferior alveolar (nerve) canal [29,36,63], is located in the spongy bone of the mandible and is available for diagnosis only by imaging techniques using X-rays [1, 3, 8, 20-22, 29, 32, 66]. Panoramic images acquired with classical and digital techniques, or increasingly popular computed tomography are clinically relevant [3,8,43,67]. Panoramic radiography is part of the standard dental diagnostics procedure performed before planning treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The high spatial resolution of CBCT provides detailed anatomical information regarding the canals and foramina located within the mandible, and has revealed many anatomical variants [ 28 , 29 ]. The frequency of these anatomical variations in CBCT scans varies among ethnic groups, with higher incidence among Asians than Caucasians [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of these anatomical variations in CBCT scans varies among ethnic groups, with higher incidence among Asians than Caucasians [ 28 ]. However, unexpected anatomical variants of foramina and canals of the mandible have also been described in Caucasians [ 28 , 29 ]. Therefore, preoperative planning based on CBCT should help oral and dental surgeons avoid iatrogenic complications during any surgical procedures involving the mandible.…”
Section: Introductionmentioning
confidence: 99%